----- - ------ 2a -2 1 - a 5 3 ----- - ------ 2x - 4 2 - x need a little understanding on these anyone? I don't understand the second term. Is it this? 3 2 ----- - ------ = 2a -2 1 - a 3 2 ----- - ------ = 2(a -1) 1 - a 3 2 ----- - ------ = 2(a -1) -( a-1) 3 2 3/2 +2 ----- + ------ = ----------------- 2(a -1) (a-1) (a-1) 4.5/(a-1) Same principles on the second, get a common denominator. oops, type, that is a 3.5 in the numerator.

First Name

Your Answer

You can ask a new question or browse existing questions.